Comparison between Neutrophil Lymphocyte Ratio and Derived Neutrophil Lymphocyte Ratio as the Risk Factor of COVID-19 - Dwi Aryani; Dea Noviana Pramatik (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Respiratory disorders were the most common sign and symptom of COVID-19. Inflammation on SARS-CoV-2 infection is presumed to play a role in the pathogenesis of COVID-19. The Neutrophil Lymphocyte Ratio (NLR) is one of many biomarkers that has been widely used to assess the risk factors of COVID-19. The derived Neutrophil Lymphocyte Ratio (d-NLR) is a simple, inexpensive, and widely available inflammation biomarker. However, its usage for COVID-19 remains to be further studied. This study aimed to determine the NLR and d-NLR ratio as a risk factor of COVID-19. This study was a retrospective study with a study population of 84 subjects, consisting of 33 patients with positive COVID-19 and 51 patients with negative COVID-19. The result showed that the odds ratio of NLR to COVID-19 was 2.665 with the p-value of 0.047 and confidence interval of 95% 0.998-7.038 at cut-off â‰¥ 3.1. The odd ratio of d-NLR to COVID-19 was 2.808 with the p-value of 0.026 and confidence interval of 95% 1.129-7.038 at cut-off â‰¥ 2.0. In conclusion, despite a higher odd ratio of d-NLR compared to NLR, both NLR and d-NLR can be used as a biomarker for the risk factor of COVID-19.